Practical recommendations to combine small-molecule inhibitors and direct oral anticoagulants in patients with nonsmall cell lung cancer. (15th June 2022) - Otten, Leila S.; Piet, Berber; van den Heuvel, Michel M.; Marzolini, Catia; van Geel, Robin M.J.M.; Gulikers, Judith L.; Burger, David M.; Leentjens, Jenneke; ter Heine, Rob
Background: The risk for thromboembolisms in nonsmall cell lung cancer (NSCLC) patients is increased and often requires treatment or prophylaxis with direct oral anticoagulants (DOACs). Small-molecule inhibitors (SMIs) to treat NSCLC may cause relevant drug–drug interactions (DDIs) with DOACs. Guidance on how to combine these drugs is lacking, leaving patients at risk of clotting or bleeding. Here, we give practical recommendations to manage these DDIs. Methods: For all DOACs and SMIs approved in Europe and the USA up to December 2021, a literature review was executed and reviews by the US Food and Drug Administration and European Medicines Agency were analysed for information on DDIs. A DDI potency classification for DOACs was composed and brought together with DDI characteristics of each SMI, resulting in recommendations for each combination. Results: Half of the combinations result in relevant DDIs, requiring an intervention to prevent ineffective or toxic treatment with DOACs. These actions include dose adjustments, separation of administration or switching between anticoagulant therapies. Combinations of SMIs with edoxaban never cause relevant DDIs, compared to more than half of combinations with other DOACs and even increasing to almost all combinations with rivaroxaban. Conclusions: Combinations of SMIs and DOACs often result in relevant DDIs that can be prevented by adjusting the DOAC dosage, separation of administration or switching between anticoagulants. Lung cancer patients treated with targeted therapy often develop thromboembolic events requiring direct oral anticoagulants (DOACs). This article provides practical recommendations on how to safely combine DOACs and targeted therapies. https://bit.ly/382NBZ1